2021
DOI: 10.1056/nejmoa2105675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Substitution on Cardiovascular Events and Death

Abstract: BACKGROUNDSalt substitutes with reduced sodium levels and increased potassium levels have been shown to lower blood pressure, but their effects on cardiovascular and safety outcomes are uncertain. METHODSWe conducted an open-label, cluster-randomized trial involving persons from 600 villages in rural China. The participants had a history of stroke or were 60 years of age or older and had high blood pressure. The villages were randomly assigned in a 1:1 ratio to the intervention group, in which the participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
356
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 394 publications
(409 citation statements)
references
References 22 publications
6
356
0
6
Order By: Relevance
“…There is insufficient evidence regarding the effects of low-sodium salt on the occurrence of hyperkalemia, largely due to ethical issues related to enrolling participants with kidney disease in trials in which they would be exposed to potassium [17]. However, many studies excluded participants based on a self-reported history of chronic kidney disease [19,21,39] and therefore may have included individuals with advanced CKD who were unaware of their disease status. A large-scale trial on low-sodium salt that followed 21,000 high-risk adults in China over five years reported no increased risk of serious adverse events attributable to low-sodium salt use [21].…”
Section: Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…There is insufficient evidence regarding the effects of low-sodium salt on the occurrence of hyperkalemia, largely due to ethical issues related to enrolling participants with kidney disease in trials in which they would be exposed to potassium [17]. However, many studies excluded participants based on a self-reported history of chronic kidney disease [19,21,39] and therefore may have included individuals with advanced CKD who were unaware of their disease status. A large-scale trial on low-sodium salt that followed 21,000 high-risk adults in China over five years reported no increased risk of serious adverse events attributable to low-sodium salt use [21].…”
Section: Safetymentioning
confidence: 99%
“…However, many studies excluded participants based on a self-reported history of chronic kidney disease [19,21,39] and therefore may have included individuals with advanced CKD who were unaware of their disease status. A large-scale trial on low-sodium salt that followed 21,000 high-risk adults in China over five years reported no increased risk of serious adverse events attributable to low-sodium salt use [21]. The trial excluded patients using potassium-sparing diuretics or potassium supplements and patients with serious kidney disease.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…1 Recent evidence has further confirmed the benefits of salt substitutes in terms of reduced rates of stroke, major cardiovascular events, and death. 2 The study by Liu et al 3 explores the acceptability of, and adherence to, a salt substitute as well as the barriers to sodium reduction. In this mixed-methods investigation conducted in rural China, participants from the Salt Substitute and Stroke Study were used.…”
mentioning
confidence: 99%
“…Given the jurisdiction specific issues that may need to be addressed, I would have thought a broader search may beneficial. For example, Neal et al (2021) 1 is a great example of linkage to RCD in China.…”
mentioning
confidence: 99%